Ab initio simulations of two‐dimensional electronic spectra: The SOS//QM/MM approach. Issue 2 (10th July 2013) - Rivalta, Ivan; Nenov, Artur; Cerullo, Giulio; Mukamel, Shaul; Garavelli, Marco
<x xml:space="preserve">Abstract</x> Two‐dimensional electronic spectroscopy (2DES) is a cutting‐edge technique for investigating with high temporal resolution energy transfer, structure, and dynamics in a wide range of systems in physical chemistry, energy sciences, biophysics, and biocatalysis. However, the interpretation of 2DES is challenging and requires computational modeling. This perspective provides a roadmap for the development of computational tools that could be routinely applied to simulate 2DES spectra of multichromophoric systems active in the UV region (2DUV) using state‐of‐the‐art ab initio electronic structure methods within a quatum mechanics/molecular mechanics (QM/MM) scheme and the sum‐over‐states (SOS) approach (here called SOS//QM/MM). Multiconfigurational and multireference perturbative methods, such as the complete active space self‐consistent field and second‐order multireference perturbation theory (CASPT2) techniques, can be applied to reliably calculate the electronic properties of multichromophoric systems. Hybrid QM/MM method and molecular dynamics techniques can be used to assess environmental and conformational effects, respectively, that shape the 2D electronic spectra. DNA and proteins are important biological targets containing UV chromophores. We report ab initio simulation of 2DUV spectra of a cyclic tetrapeptide containing two interacting aromatic side chains, a model system for the study of protein structure and dynamics by means of 2DUV spectroscopy. © 2013 Wiley Periodicals, Inc.